2015
DOI: 10.1093/ecco-jcc/jjv180
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Healing in Ulcerative Colitis – When Zero is Better

Abstract: In patients with UC in corticosteroid-free remission, particularly those with left-sided colitis or extensive colitis, MES 1 was significantly associated with a 3-fold increased risk of relapse compared with endoscopic MES 0. Our results support the use of endoscopic MES 0 as the most suitable treatment endpoint to define mucosal healing in patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 48 publications
5
59
0
2
Order By: Relevance
“…Importantly, we observed that achieving histologic remission may be most relevant in patients who have mild endoscopic activity, whereas its benefit in patients who achieve complete endoscopic remission may have less impact on shorter terms outcomes, requiring a longer time horizon of follow up to identify benefit. However, prior studies have demonstrated benefit of achieving histologic remission, even in patients who achieve complete endoscopic remission 12‐16 . These differences may be related to variability in patient characteristics including the proportion of patients with high‐and low‐risk disease and the accuracy of diagnosing MES 0 vs MES 1 in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we observed that achieving histologic remission may be most relevant in patients who have mild endoscopic activity, whereas its benefit in patients who achieve complete endoscopic remission may have less impact on shorter terms outcomes, requiring a longer time horizon of follow up to identify benefit. However, prior studies have demonstrated benefit of achieving histologic remission, even in patients who achieve complete endoscopic remission 12‐16 . These differences may be related to variability in patient characteristics including the proportion of patients with high‐and low‐risk disease and the accuracy of diagnosing MES 0 vs MES 1 in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show a difference in transcription between the Mayo endoscopic score (MES) of 0 and 1. Previous papers have shown that a MES of 0 gives a favorable outcome in relation to clinical remission rates [17][18][19]. All genes that were differentially transcribed were up-regulated in MES 1.…”
Section: Discussionmentioning
confidence: 82%
“…Our novel imaging-enhanced endoscopic system with MAGIC score could become one of the non-invasive, objective and quantitative modalities for detailed evaluation of MH in patients with UC. Recently, endoscopic evaluation of UC disease activity has become more important and essential because the treatment goal for UC has shifted from controlling symptoms during clinical remission to achieving endoscopic remission, i. e. MH [26]; however, the term MH is considered ambiguous because there is no validated definition of MH in UC patients for either endoscopic or histologic examinations. MES is widely used to evaluate endoscopic disease activity in clinical practice and trials, because it is easy to assess, and an MES of 0 or 1 is often defined as MH; however, several studies have demonstrated a wide difference in the UC relapse rate between patients with MES 0 and those with MES 1 [7,8].…”
Section: Discussionmentioning
confidence: 99%